Faculty of Business and Management is moving forward with international collaborations through expert forum sharing session - UiTM, Faculty of Business and Management (UiTM, 2023)
The Faculty of Business and Management (FBM) is advancing its international collaborations through an expert forum sharing session. The event provided a platform for knowledge exchange with international experts, fostering academic excellence, research development, and global networking opportunities for the faculty.